2015
DOI: 10.3389/fvets.2015.00035
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Plant Essential Oils and Their Components in Animal Agriculture – in vitro Studies on Antibacterial Mode of Action

Abstract: The antimicrobial activity of essential oils and their components has been recognized for several years. Essential oils are produced as secondary metabolites by many plants and can be distilled from all different portions of plants. The recent emergence of bacteria resistant to multiple antibiotics has spurred research into the use of essential oils as alternatives. Recent research has demonstrated that many of these essential oils have beneficial effects for livestock, including reduction of foodborne pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 65 publications
4
67
0
Order By: Relevance
“…Gram-negative bacteria are generally very resistant to the antibacterial properties of the essential oils. The hydrophobic components of essential oils are able to affect Gram-negative bacteria by gaining the access through the periplasm of the porin protein in the outer membrane which eventually allows essential oils to travel inside the cells of the bacterium (Helander et al, 1998;O'bryan et al, 2015;Plésiat and Nikaido, 1992). According to Deans and Ritchie (1987) and Deans et al (1995), the inhibitory effect of essential oil is weakly correlated to whether the bacteria is Grampositive or Gram-negative, this observation is supported by present study.…”
Section: Antibacterial Activities Of Selected Essential Oilssupporting
confidence: 78%
“…Gram-negative bacteria are generally very resistant to the antibacterial properties of the essential oils. The hydrophobic components of essential oils are able to affect Gram-negative bacteria by gaining the access through the periplasm of the porin protein in the outer membrane which eventually allows essential oils to travel inside the cells of the bacterium (Helander et al, 1998;O'bryan et al, 2015;Plésiat and Nikaido, 1992). According to Deans and Ritchie (1987) and Deans et al (1995), the inhibitory effect of essential oil is weakly correlated to whether the bacteria is Grampositive or Gram-negative, this observation is supported by present study.…”
Section: Antibacterial Activities Of Selected Essential Oilssupporting
confidence: 78%
“…As a result of membrane permeability, all other cellular functions including membrane potential, efflux pump activity or respiratory activity are also compromised [16]. Moreover, it has been evidenced, using flow cytometry experiments, that the mode of action mediated by bacterial cell permeabilization is similar in both Gram-positive and negative bacteria [17].…”
Section: Cytotoxicity Activitymentioning
confidence: 94%
“…It has been reported that the hydrophobicity of the essential oils produce changes in bacterial membrane structure and wall structures. Alteration of the cell permeability, disturbance to respiration, modification of bacterial quorum sensing, potassium leakage from cells, effects on membrane potential (proton translocation), changes in pH gradient and ATP production of bacterial cell bacterial lipid membrane, lead to the lysis and death of bacteria (O'Bryan et al, 2015). On the other hand, the effect of essential oil of T. vulgaris on biofilm formation of uropathogenic E. coli was determined.…”
Section: Discussionmentioning
confidence: 99%